2003
DOI: 10.1063/1.1622781
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring structure and electrical properties of carbon nanotubes using kilo-electron-volt ions

Abstract: We report the effects of 30 and 50 keV Ga+ ion irradiation on the structure and electrical properties of arc-evaporated multiwalled carbon nanotubes (MWNTs). For 50 keV ions with doses of ∼1013 ions/cm2 the outer shells of the MWNTs remain intact, while the inner layers reorganize into highly ordered pillbox-like ∼5-nm-diam nanocompartments of varying lengths between 2 and 20 nm. Increasing the dose to ∼1014 ions cm−2 results in the gradual disordering of the graphitic shells and destroys the nanocapsules, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 22 publications
3
50
0
Order By: Relevance
“…Irradiation of arc-evaporated MWNTs with 30 and 50 keV Ga ions resulted in very interesting structural transformations in the nanotubes. 22 For 50 keV ions with doses of ϳ10 13 ions/ cm 2 , the outer shells of the MWNTs remained intact, while the inner layers reorganized into highly ordered pillboxlike nanocompartments with diameters of about 5 nm and of varying lengths between 2 and 20 nm, see Fig. 44 34 as well.…”
Section: Experiments On Heavy Ion Irradiation Of Carbon Nanotubesmentioning
confidence: 98%
See 1 more Smart Citation
“…Irradiation of arc-evaporated MWNTs with 30 and 50 keV Ga ions resulted in very interesting structural transformations in the nanotubes. 22 For 50 keV ions with doses of ϳ10 13 ions/ cm 2 , the outer shells of the MWNTs remained intact, while the inner layers reorganized into highly ordered pillboxlike nanocompartments with diameters of about 5 nm and of varying lengths between 2 and 20 nm, see Fig. 44 34 as well.…”
Section: Experiments On Heavy Ion Irradiation Of Carbon Nanotubesmentioning
confidence: 98%
“…[6][7][8][9][10][11][12][13][14][15][16] Besides, it was demonstrated that nanotubes can be interconnected or merged 9,12,17,18 and that irradiation can give rise to many interesting phenomena, such as extreme pressure inside nanotubes 19 or fullerenelike "onions," 6,20 so that these systems can be used as nanolaboratories for studying pressure-induced transformations at the nanoscale. Furthermore, recent experiments indicate that ion, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] electron, 6,39-52 and high energy photon [53][54][55][56] irradiation can be used to tailor the mechanical, 8,10 electronic, 11,[21][22][23] and even magnetic …”
Section: Introductionmentioning
confidence: 99%
“…Band gap tailoring and carbon nanotube interconnects have been achieved using charged particle beams as well. [4][5][6][7] Furthermore, it appears that it is possible to modify their physical properties by changing their structure locally only along a short section of the tube. 8 Most of the works devoted to study the effects of electron or ion-beam irradiation have involved single-walled and multiwalled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Ion or electron beam irradiation may also be a possible way [30]. For example, after Ga + ion irradiation, the housing tube becomes positively charged [31].…”
Section: Nano Researchmentioning
confidence: 99%